Associations between high-density lipoprotein cholesterol, non-high-density lipoprotein cholesterol, and their ratio with metabolic dysfunction-associated steatotic liver disease: a retrospective cohort study - Chen, Hong; Miao, Xinlei; Hu, Manling; Song, Ziping; He, Yangxuan; Deng, Jiayi; Leng, Song (Frontiers in Endocrinology, 2025)
ObjectiveHigh-density lipoprotein cholesterol (HDL-C), non-HDL-C, and the ratio of non-HDL-C to HDL-C (NHHR) are closely correlated with multiple metabolic diseases. This study aims to dissect their associations and differences in relation to new-onset MASLD.MethodsData were collected from research subjects at the Health Management Center of the Second Affiliated Hospital of Dalian Medical University between 2014 and 2023. Participants were stratified by quartiles of HDL-C, non-HDL-C, and NHHR. Kaplan–Meier analysis, Cox proportional hazards models, restricted cubic splines (RCS), sensitivity analyses, and receiver operating characteristic (ROC) curves were employed to evaluate associations between NHHR, non-HDL-C, HDL-C, and new-onset MASLD and compare predictive performance across lipid parameters.ResultsA total of 36,897 participants (mean age 42.1 years; 56.5% female) were followed for a mean of 3.19 years, with 20.3% developing new-onset MASLD. Cox regression showed that compared to the Q1 group, the Q4 group of NHHR and non-HDL-C had a 134% (HR=2.34, 95% CI: 2.13–2.56) and 22% (HR=1.22, 95% CI: 1.13–1.31) higher risk of MASLD, respectively, while HDL-C was associated with a 45% lower risk (HR=0.55, 95% CI: 0.50–0.60). RCS analysis demonstrated nonlinear relationships for NHHR (threshold = 2.54) and HDL-C (threshold = 1.31 mmol/L), whereas non-HDL-C displayed a linear, positive association with MASLD risk. Stratified analyses revealed that elevated non-HDL-C levels conferred higher MASLD risk in men, whereas females, younger adults, and individuals with lower cardiometabolic burden (BMI <24 kg/m², nonhypertensive, and nonhyperuricemic status) showed steeper increases in MASLD risk with rising NHHR quartiles. ROC analysis indicated NHHR was superior to other lipid parameters in predicting MASLD risk.ConclusionDecreases in HDL-C levels and increases in non-HDL-C and NHHR levels may increase the risk of MASLD. The NHHR can be used as a new index that is stronger than other lipoproteins for the prediction of MASLD.